Confidence and Spontaneity in an Intensive EFL Speaking Program: An Outcome-Focused Logic Evaluation - Saini, Fadhlan; Padmadewi, Ni Nyoman; Utami, I GA Lokita Purnamika; Suarcaya, Putu (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Confidence and spontaneity are often treated as expected outcomes of EFL speaking programs, yet program evaluations rarely explain how these outcomes are produced, sustained, or limited by classroom processes. Addressing this gap, this study evaluated a Basic Speaking Class through an outcome-focused logic evaluation framework to examine how program inputs, communicative activities, classroom conditions, and immediate outcomes shaped students’ oral development. This qualitative evaluative case study involved 12 participants: 10 students, one speaking lecturer, and one program coordinator. Data were collected through semi-structured interviews, classroom observation with field notes, and program documents, and were analyzed thematically using the logic framework as an analytical lens. The findings show that communicative tasks such as games, role plays, discussions, and problem-solving activities, when supported by peer interaction and responsive feedback, created a less threatening space for students to take risks, speak more willingly, and rely less on memorized scripts. However, these gains were context-dependent. Students’ confidence and spontaneity were strongest in low-stakes classroom interaction but weakened in formal academic speaking situations, particularly when vocabulary recycling, task progression, and tutor scaffolding were insufficient. The study contributes to EFL speaking program evaluation by showing that confidence and spontaneity are not automatic indicators of program success, but developmental and fragile outcomes shaped by the alignment between task design, classroom support, and transfer-oriented speaking practice.